Markers of blood-brain barrier disruption increase early and persistently in COVID-19 patients with neurological manifestations - Bonetto, Valentina; Pasetto, Laura; Lisi, Ilaria; Carbonara, Marco; Zangari, Rosalia; Ferrari, Erica; Punzi, Veronica; Luotti, Silvia; Bottino, Nicola; Biagianti, Bruno; Moglia, Cristina; Fuda, Giuseppe; et al. (Frontiers in Immunology, 2022)
Background. Coronavirus disease 2019 (COVID-19) caused by SARS-CoV-2 infection is associated with disorders affecting the peripheral and the central nervous system. A high number of patients develop post-COVID-19 syndrome with the persistence of a large spectrum of symptoms, including neurological, beyond 4 weeks after infection. Several potential mechanisms in the acute phase have been hypothesized, including damage of the blood-brain-barrier (BBB). We tested weather markers of BBB damage in association with markers of brain injury and systemic inflammation may help in identifying a blood signature for disease severity and neurological complications. Methods. Blood biomarkers of BBB disruption (MMP-9, GFAP), neuronal damage (NFL) and systemic inflammation (PPIA, IL-10, TNFα) were measured in two COVID-19 patient cohorts with high disease severity (ICUCovid; n=79) and with neurological complications (NeuroCovid; n=78), and in two control groups free from COVID-19 history, healthy subjects (n=20) and patients with amyotrophic lateral sclerosis (ALS; n=51). Samples from COVID-19 patients were collected during the first and the second wave of COVID-19 pandemic in Lombardy, Italy. Evaluations were done at acute and chronic phases of the COVID-19 infection. Results. Blood biomarkers of BBB disruption and neuronal damage are high in COVID-19 patients with levels similar to or higher than ALS. NeuroCovid patients display lower levels of the cytokine storm inducer PPIA but higher levels of MMP-9 than ICUCovid patients. There was evidence of different temporal dynamics in ICUCovid compared to NeuroCovid patients with PPIA and IL-10 showing the highest levels in ICUCovid patients at acute phase. On the contrary, MMP-9 was higher at acute phase in NeuroCovid patients, with a severity dependency in the long-term. We also found a clear severity dependency of NFL and GFAP levels, with deceased patients showing the highest levels. Discussion The overall picture points to an increased risk for neurological complications in association with high levels of biomarkers of BBB disruption. Our observations may provide hints for therapeutic approaches mitigating BBB disruption to reduce the neurological damage in the acute phase and potential dysfunction in the long-term.